Integration of associative board games into the university learning process when studying media literacy (using the example of the board game «Media Labyrinth») - Taishybai , З.С.; Shaikenova, А.Ж.; Chinishlov , В.В. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2024)
The presented research paper examines the phenomenon of gamification, its importance for the educational process in higher educational institutions of the Republic of Kazakhstan, where work is systematically carried out to improve the level of media literacy of students, undergraduates of faculties and departments of journalism. The main purpose of this publication is to describe the game mechanisms that are most suitable for introduction into the educational process in the study of media literacy. According to the authors, these include a set of rules and designations underlying verbal and team associative games. Using a number of successful ideas of modern game design in the above direction, the team of the Department of Journalism of a regional university created an educational board game «Media Labyrinth». The theoretical significance of the article lies in the fact that the data revealed during the research can be used by teachers of higher educational institutions of the Republic of Kazakhstan in the process of writing research papers, teaching aids within the framework of the studied issues, as well as in the preparation of lecture materials on the discipline «Media Literacy». The practical significance of this scientific work lies in the possibility of introducing the research results into the educational process in higher education (using the board game «Media Labyrinth» in the practical classes of journalism students). At the same time, the board game «Media Labyrinth» has the potential to become a universal means of increasing the level of media literacy, since it can have a positive impact not only on students studying Journalism, but also on students of other humanities, high school students with in-depth study of information technology.